Development and characterization of dried shrimp (Acetes sp.) as kalkag mix for sinangag. - Nanas, Nima Sherine Antolo (2016.)
The study focused on developing a sinangag mix from dried shrimps (Acetes sp.), kalkag in Region 6. Shrimps were dried together with other ingredients: garlic, red onion and red bell pepper. Blanching of shrimps before drying was found to be significantly affect its overall acceptability. Among the three formulations: KMFI (250 g dried shrimp: 50 g dried garlic: 50 g dried red onion: 20 g dried red bell pepper), KMF2 (250 g dried shrimp: 5o g dried garlic: 30 g dried red onion: 10 g dried red bell pepper) and KMF3 (250 g dried shrimp: 50 g dried garlic: 10 g dried red onion: 0 g dried red bell pepper), KMF2 was significantly the most preferred. Product from KMF2, designated as kalkag mix MPF was subjected to water activity determination, sensory, proximate, and microbiological analysis. Line scale revealed that kalkag (11.710 cm) dominated the aroma of kalkag mix MPF followed by dried garlic (7.967 cm), red onion (5.031 cm) and bell pepper (3.740 cm). Kalkag mix MPF had 8.421% moisture content, 56.166% protein, 3.091% fat, 10.670% ash, 2.663% crude fiber and 18.990% carbohydrates. Water inactivity of the product was 0.423. Coliforms (>1100 MPN/g) and E. coli were detected in uncooked kalkag mix MPF. Sauteing effectively eliminated all coliforms rendering the product safe for consumption. The Yeast and Mold Count for the trial 1 (2.65 x 102 CFU/g) were lower than the maximum count beyond which product safety/quality may be affected (10000 CFU/g; PNS and BFAD, 2006). Among the three ratios of kalkag mix MPF to cooked rice: R1 (1:3), R2 (1:4) and R3 (1:5), R2 was significantly the most preferred (Kramer?s Rank Sum Test at 5% level of significance). Sinangag with kalkag mix from R2 was rated moderately like. Among the 100 consumers, 37% rated moderately like, 36% like very much, 21% slightly like, 4% neither like nor dislike and 2% rated slightly dislike. Overall, 73% rated the sinangag with kalkag mix MPF like moderately to like very much. Thus, the kalkag mix MPF for sinangag has high market potential.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Dried shrimp; Acetes sp; Kalkag mix; Sinangag